Analisis Strategi Komunikasi Pemasaran Nronlineshop_ Di Platform Shopee - Nadya Rahmadhani; Dilla Syadzwina; Jois Simarmata; Lenti Susanna Saragih; Danny Ajar Baskoro (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research analyzes the marketing communication strategy used by Nronlineshop_ on the Shopee e-commerce platform. In the rapidly developing digital era, marketing communication strategy is a key factor in determining the success of an online business. Its aim is to increase visibility, sales, and customer loyalty with effective and efficient strategies. The research employs a method of library study and a qualitative approach, focusing on theory and a case study of Nronlineshop_. The findings show that Nronlineshop_ implements a strategy that includes promotional tools in marketing communication such as advertising, sales promotion, public relations, personal selling, and direct marketing. The main challenge is the intense competition on Shopee, necessitating better product and service differentiation. The recommendations given include developing differentiation strategies, collaborating with influencers, integrating marketing channels, and understanding technology trends.